The Role of Extremist Groups in Fueling Violence in Sudan - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2023)
In this paper we consider the role extremist groups play in perpetuating violence in Sudan, a country long plagued by terrorism and political instability. We examine the various groups’ ideologies, world views, and objectives, and discuss the influence these groups have on the social, political, and economic welfare of Sudan. Starting with an historical overview, we explain how extremism in Sudan first took root. We examine the primary players and their regional and international influences. Further, we examine the significant toll extremist-driven violence has taken and continues to take on civilian population as well as on governance and the economy. Furthermore, we study the ways Sudanese government has attempted to disempower extremist groups and analyze the effectiveness of international interventions. By analyzing the root causes of extremism as well as current events, we seek to provide a thoughtful land nuanced understanding of this pernicious issue. This study serves as a critical examination of the complexities surrounding extremist violence in Sudan, contributing to the broader discourse on counterterrorism and peacebuilding in conflict-prone regions.